SIZE REDUCTION AND DENSIFICATION OF HERBACEOUS BIOMASS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
Herbaceous biomass can be obtained using delayed harvesting method with moisture content less than 15% and directly densified without drying. Size reduction experiments of common reed stalks as cutting, flattening and densification have been carried out. As the result of reed stalk flattening, more than 8 strips can be obtained from this tubular structure. Average energy consumption 273 – 380 J kg-1 had been stated for reed stalk flattening. Specific cutting energy Escq value varies in 8 – 16 kJ m-2 in dependence of punch orientation angle according cross-section of reed specimen. Specific cutting energy for flattened stalk materials for reed density 600 kg m-3, varies Esc=13.3 – 27 J m kg-1. Densification experiments of compositions from peat particles, coarse wheat stalk and reed material particles from (1 - 2 mm) group with pressure 230 MPa indicated influence of peat proportion. Density 1.0 g cm-3 has been obtained in densification of straw stalk material particle compositions with peat, if peat proportion exceeds 20%.